2008
DOI: 10.1111/j.1749-8198.2008.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainable Suburban High Street: A Review of Themes and Approaches

Abstract: Whether suburbs are regarded as a distinctive feature of the contemporary urban landscape or as symptomatic of 'sprawl' the recent upsurge of scholarly interesting suburbia has done little to displace the dominant image of the suburb as primarily residential phenomenon. In a wide ranging survey of the academic literature, taking account of current developments in the policy debate relating to suburban regeneration and also drawing on research conducted by the Engineering and Physical Sciences Research Council'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…The subsequent development of the railways in the nineteenth century and the twentieth-century growth of private motor car ownership (and the subsidy of road building by governments in the USA) had equally important impact both spatially and socially. 1 Existing settlements such as Hampstead, although originally outside of the urban conurbation, helped to mitigate the rawness of London's suburban development, so that main roads which formerly might contain linear developments of coaching inns, shops and villas, subsequently were in an ideal position to develop as London's network of high streets (Griffiths et al 2008;Carmona 2015). This process is illustrated by a painting from c.1830 by John Constable (Figure 1.2).…”
Section: Meta Berghauser Pont Is Senior Lecturer In Urbanmentioning
confidence: 99%
“…The subsequent development of the railways in the nineteenth century and the twentieth-century growth of private motor car ownership (and the subsidy of road building by governments in the USA) had equally important impact both spatially and socially. 1 Existing settlements such as Hampstead, although originally outside of the urban conurbation, helped to mitigate the rawness of London's suburban development, so that main roads which formerly might contain linear developments of coaching inns, shops and villas, subsequently were in an ideal position to develop as London's network of high streets (Griffiths et al 2008;Carmona 2015). This process is illustrated by a painting from c.1830 by John Constable (Figure 1.2).…”
Section: Meta Berghauser Pont Is Senior Lecturer In Urbanmentioning
confidence: 99%
“…Potential shoppers must be prepared to share their shopping requirements, and retailers must be prepared to participate in an EasiShop hotspot network. A detailed description of EasiShop may be found elsewhere (Keegan et al, 2008); however a short summary of its features and modus operandi is provided here.…”
Section: The Easishop Experiencementioning
confidence: 99%
“…Though no two situations are exactly alike in the challenges they have to overcome, certain commonalities exist, and these have emerged for the most part within the last thirty years. In the former instance, the growth of out-of-town shopping and of corporate retailers has radically altered the traditional shopping experience (Griffiths et al, 2008). Likewise, increased car ownership, changes in lifestyles and the arrival of internet-based e-commerce have altered consumer behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…They encourage sustainable mobility, economically support their neighbourhoods, offer a safe public realm, facilitate social inclusion, enhance a local identity and encourage social life (Jones et al 2007). However, as pointed out by Griffiths et al (2008Griffiths et al ( : 1158, both the academic and policy-oriented literature has conventionally measured the socio-economic health of traditional suburban centres based on their 'vitality' (pedestrian activity) and 'viability' (the ability to attract investment). Indeed, it is broadly assumed that lively streets and active ground-floor businesses are symptomatic of successful urban tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The sample for this research was drawn from an earlier study which focused on a sample of twenty smaller town centres from around London's periphery, 1 selected in order to study cases which have existed since the late nineteenth century and have survived social, economic and physical change whilst maintaining a mix of commercial and other town centre related activities. The earlier study found that these smaller centres are a vital background of activity to the larger outer London centres, forming part of an interdependent network (Griffiths et al 2008). The final criterion for choosing the four cases was that they should be distributed across the London city-region so that they would be representative of urban growth occurring in all directions away from the centre of London and so help to identify any differences this may have brought to their developmental trajectories.…”
Section: Introductionmentioning
confidence: 99%